Pengaruh Kompetensi, Akuntabilitas dan Etika Auditor terhadap Kualitas Audit (Studi Kasus terhadap Persepsi Auditor BPKP Provinsi Kalimantan Timur) - Kristi Paskalia; Irwansyah Irwansyah; Bramantika Oktavianti (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2017)
The purpose of this study is to analyze and test the effect of Auditor’s competence, accountability and ethics to audit quality. In this study, the research data obtained through questionnaires distributed to respondents. The sample used in this study is a certified auditor who has a functional position as many as100 employees. Questionnaires are 100 in total distributed, while the ones that can be used are 40 questionnaires and The analysis tool in this study is Partial Least Square (PLS) SmartPLS version 2. Based on the calculation of structural equation model (inner model), it is known that the competence variable (X1) obtained t-statistic of 2.1364411.96. The value of the original sample is positive estimate of 0.238108, which means the competency has positive significant effect on audit quality. Accountability of the variables (X2) obtained by the t-statistic of 3.4666981.96. The value of the original sample is positive estimate of 0.389689, which means the accountability has positive significant effect on audit quality. While the auditor ethics variable (X3) obtained t-statistic of 9.1902331.96. The original value estimate is a positive sample for auditor ethics 0.403091, which means a significant positive effect on audit qualityKeywords: competence, accountability, ethical auditors, audit quality